PUBLIC RELATIONS STRATEGY IN ADDRESSING CRISIS ON IMAGE OF LION AIR AIRLINES IN PEKANBARU - Koestriandri "; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The Lion Air Airline was founded in 2000, is one of the pioneers ofcommercial aviation in Indonesia. Lion Air is one of the air transportation of non-governmental early generations who have managed to get through the crisis and hasgrown rapidly to face the competition by developing organizational, operationalcapabilities and also its fleet. The actual case is less rapid handling of the crisis wasmade by the Lion Air Pekanbaru. The purpose of this study was to determine how thepublic relations strategy in handling the crisis at the image of Lion Air in Pekanbaru,as well as factors related to the public relations strategy in handling the crisis at theLion Air in Pekanbaru.This study used qualitative methods with descriptive approach, which is aproblem-solving procedures are investigated, by describing / depicting the object ofresearch at the present time. Based on the facts that appear or as they are, while theframework uses a model of Strategic Communications.The results of this study indicate that public relations strategies conducted byLion Air Pekanbaru. They have a strategy for dealing with image crisis include:strategies to identify the issues that led to the crisis, map the needs of reporters duringa crisis, prepare information for management, and have the image enhancementstrategies include flight scheduling, fleet use of new, lower price , and using themethod of a press conference to facilitate imaging convey messages to the public.Lion Air branch of Pekanbaru also use existing media in the city of Pekanbaru, suchas Riau Pos, and electronic media such as aditiya FM, and in collaboration with aleading telecommunications company Telkomsel.Keyword : Communication, Strategy, Crisis